DESAIN PEMBELAJARAN BAHASA INDONESIA BERBASIS PEMAHAMAN NILAI SIKAP GOTONG ROYONG - Alpansyah, Alpansyah; Hasim, Abdul Talib (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
The aims of this study were: (1) to identify an increase in students' understanding of the value of mutual cooperation through the use of reader response rules in Indonesian Language Learning (KRPDPBI); (2) identifying the use of the reader response principle in Indonesian Language learning (KRPDPBI) there are differences between male and female students. The design of this study used a quasi-experimental study with two different methods. The results showed that (1) the achievement of the score of understanding the value of mutual cooperation for students taught by KRPDPBI was better than for students taught by regular learning according to the curriculum; (2) the achievement of the understanding of the value of male students' mutual cooperation is no better than that of female students.